A Proposal for the Governance of Financial Regulation and Supervision in Europe - Armin J. Kammel (Vierteljahrshefte zur Wirtschaftsforschung, 2005)
Financial markets underwent significant changes worldwide within the last decades. Structural changes involving traditional operators led to modifications of the regulatory as well as supervisory settings of the financial system. Therefore, the paper tries to find a solution for a proper and well functioning regulatory and supervisory framework for the European single market. In this context, some pragmatic ideas regarding the reorganization of the regulatory arrangements and supervisory settings of financial markets in the European Union are presented. Moreover, the paper tries to point out that it is too early to establish a single European supervisory authority. As the paper shows, it might be useful to make use of the gradually implemented Lamfalussy architecture and simply add one more committee which has the task to coordinate the activities of the four within the Lamfalussy architecture proposed committees. The institutional design of this committee is quasicentralized. The advantage of the proposal is that the institutional framework is characterized by a high degree of flexibility, meaning that its institutional arrangements can be transformed into a centralized supervisory authority and that it is cost-efficient since it is partly based on partly already existing structures. – – Die internationalen Finanzmärkte erlebten in den letzten Jahrzehnten weltweit signifikante Veränderungen. Strukturelle Veränderungen, die auch traditionelle Operatoren umfassten, führten zu Modifikationen sowohl der regulatorischen als auch der aufsichtsbehördlichen Gegebenheiten des Finanzsystems. Vor diesem Hintergrund wird in diesem Papier versucht, eine angemessene und vor allem funktionierende Lösung hinsichtlich des regulatorischen und des aufsichtsbehördlichen Rahmens für den Europäischen Binnenmarkt zu finden. Dazu werden einige pragmatische Vorschläge betreffend die Reorganisation dieser Gegebenheiten des Finanzsystems in der Europäischen Union unterbreitet. Zudem wird versucht zu belegen, dass es für die Errichtung einer europäischen Finanzaufsichtsbehörde noch viel zu früh ist. Vielmehr wird angeregt, sich die Lamfalussy- Architektur zunutze zu machen und ein weiteres Komitee hinzuzufügen, dessen Aufgabe es ist, die Tätigkeiten der - im Rahmen der Lamfalussy-Architektur ins Leben gerufenen - Komitees zu koordinieren. Von einem institutionellen Blickwinkel wäre dieses Komitee quasi-zentralistischer Natur. Die Vorteile dieses Vorschlags wären die hohe Flexibilität des institutionellen Rahmens, der in eine zentrale Aufsichtsbehörde transformiert werden kann, und seine Kosteneffizienz, da auf existierende Strukturen Rücksicht genommen wird.
Keywords: 330; Finanzmarkt; Aufsichtsbehörde; EU-Staaten